Subconscious Biases in Coral Reef Fish Studies. (1st July 2020) - Bellwood, David R; Hemingson, Christopher R; Tebbett, Sterling B
Abstract: In complex, diverse ecosystems, one is faced with an exceptionally challenging decision: which species to examine first and why? This raises the question: Is there evidence of subconscious biases in study species selection? Likewise, is there evidence of this bias in selecting methods, locations, and times? We addressed these questions by surveying the literature on the most diverse group of vertebrates (fishes) in an iconic high-diversity ecosystem (coral reefs). The evidence suggests that we select study species that are predominantly yellow. Reef fish studies also selectively examine fishes that are behaviorally bold and in warm, calm, attractive locations. Our findings call for a reevaluation of study species selection and methodological approaches, recognizing the potential for subconscious biases to drive selection for species that are attractive rather than important and for methods that give only a partial view of ecosystems. Given the challenges faced by high-diversity ecosystems, we may need to question our decision-making processes.